2017
DOI: 10.1080/24750573.2017.1345084
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of unplanned complex suicide

Abstract: Suicide is defined as using more than one method to induce death. Suicides are divided into simple and complex cases. A complex suicide is defined as the use of more than one method to induce death. The planning of several methods for inducing death further permits the classification of suicide into planned and unplanned. In planned type, two or more methods are applied simultaneously to make sure that death will occur. In unplanned type, a second method is just used if the first method is unsuccessful or pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As the aforementioned cases show, decedents tend to inflict injuries via less lethal methods initially and then subsequently attempt a more lethal method. The conversion from lesser to greater lethality methods is most likely associated with antemortem pain, anguish, and frustration by the decedent (Eroglu et al, 2017). The pattern of injuries over the body is equally important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the aforementioned cases show, decedents tend to inflict injuries via less lethal methods initially and then subsequently attempt a more lethal method. The conversion from lesser to greater lethality methods is most likely associated with antemortem pain, anguish, and frustration by the decedent (Eroglu et al, 2017). The pattern of injuries over the body is equally important.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the attempted or completed suicidal act involved a single method; however, there were situations where multiple methods were used simultaneously by the decedents to commit suicide. The term “complex suicide” refers to a suicidal incident where the individual uses more than one method (Ateriya et al, 2018; Blanco-Pampin et al, 1997; Cingolani & Tsakri, 2000; Eroglu et al, 2017; Padosch et al, 2003; Taff et al, 1998; Turk et al, 2004; Viel et al, 2009).…”
mentioning
confidence: 99%
“…Salem et al (28), reported in Romania the suicide of a 76-year-old male who drilled his own chest using a drill borer. When two or more methods are applied either simultaneously or one after another in a suicide, it is called complex suicide (11,14,33). Complex suicides were reported in Turkey (11), Tunisia (14), and Romania (28).…”
Section: Suicide By Violent Methodsmentioning
confidence: 99%